The Implementation of Reading Literacy Strategies in Merdeka Curriculum Instruction for Fourth-Grade Students at SD Negeri Buniwah 01 - Indra Apriyanto; Bernadus Wahyu Joko Santoso; Haryadi; Tri Joko Raharjo (Educational Management, 2025)
This study aims to describe the implementation of reading literacy strategies in Merdeka Curriculum instruction for fourth-grade students at SD Negeri Buniwah 01, covering planning, implementation, evaluation, and the supporting and inhibiting factors faced by the teacher. A qualitative approach with a case study design was employed. The participants consisted of one fourth-grade teacher, one principal, and 25 students. Data were collected through participatory observation, in-depth interviews, and documentation, and were analyzed using Miles, Huberman, and Saldaña’s interactive model, which includes data reduction, data display, and conclusion drawing and verification. Data trustworthiness was ensured through source and technique triangulation, member checking, and the use of adequate theoretical references. The results show that the teacher planned literacy activities by integrating reading materials into teaching modules aligned with themes and learning outcomes in the Merdeka Curriculum. The main strategies used were guided reading, paired reading, and reading aloud. These strategies increased student engagement, facilitated text comprehension, and enriched vocabulary. Supporting factors included the availability of a reading corner, the principal’s commitment, and the teacher’s creativity in designing literacy activities. Inhibiting factors included limited thematic reading collections, diverse reading abilities among students, time constraints, and an uneven home reading culture. Efforts to address these obstacles involved utilizing digital reading resources, developing simplified teacher-made texts, implementing differentiated instruction, and involving parents through home reading assignments. Overall, the implementation of reading literacy strategies in Merdeka Curriculum instruction had a positive impact on students’ motivation and reading comprehension and contributed to the development of adaptive and sustainable reading literacy programs in primary schools.